Solitary extramedullary plasmacytoma presenting as an adrenal tumor: case report and literature review - Khan, Umar Zeb (Gland Surg, 2021)
Solitary extramedullary plasmacytoma, an extremely rare case which accounts for about 3% of all plasma cell neoplasms, often occurs in the head and neck region such as para nasal sinuses, nasal cavity and oral cavity, it also occurs in the lymph nodes, lungs, thyroid, intestine, liver, pancreas, testis, breast, or skin. Isolated primary plasmacytoma of adrenal is extremely rare and only nine documented cases have been reported in the literature. We are presenting the 10(th) case which is the youngest patient until now with symptoms of fever and hepatosplenomegaly. A 19-year-old female was admitted with an irregular fever for 20 days. After a series of investigations were carried out there were no CRAB symptoms (hypercalcemia, renal failure, anemia and bone lesions), no free light chain and no more than 10% increase in plasma cell on bone marrow examination. Computed tomography (CT) scan revealed a tumor in the left adrenal region, and it was diagnosed to be a solitary extramedullary plasmacytoma on biopsy. She underwent the tumor resection one month after admission and recovered well after operation without fever and was discharged from hospital on the thirteenth post-operative day. She has been followed up for 5 years without any sign and symptom of tumor recurrence. Extramedullary plasmacytoma of adrenal gland in an extremely rare disease and usually diagnosed late in life but it can present in younger patients with variable symptoms. However, the surgical treatment yields excellent long-term results. So, complete surgical resection of the lesion is not only a good diagnostic measure, but also an intent-for-cure treatment for solitary adrenal extramedullary plasmacytoma.